WEB SERIES ANIMASI NUSSA SEBAGAI MEDIA PENDIDIKAN ISLAMI PADA ANAK - Fathin Hanifah Langga; Hafiz Aziz Ahmad; Alvanov Zpalanzani Mansoor (Wimba : Jurnal Komunikasi Visual, 2019)
For moslems, Islamic education becomes a guide in life. The main purpose of Islamic education is to build moslems personalities so that human beings are moral or noble. Animation web series is a choice as well as a medium for information and community education in Indonesia. There is Nussa animation web series that takes up stories about the teachings of Islam. The purpose of this study is to determine the quality of Nussa's animation as a medium of Islamic education that is in accordance with the function of the film, the criteria for educational media based on national education goals and interpretation of the Qur'an, efforts to build the potential for religious awareness in children, and benefits as educational media. This study used descriptive qualitative method. The results of this study prove that Nussa animation has been able to meet the criteria as a medium of Islamic education in accordance with the function of the film, the criteria for educational media based on national education goals, the interpretation of the Qur'an, and its benefit. The ease of access and material on Nussa's animation as a web series is uploaded consistently every week, continuously and gradually, so that the loyal animation fans of Nussa are not stopped to get a message about Islamic education. This makes Nussa animation a very popular animation, often this animation is trending and viral in various social media. However, there are still efforts in facilitating children's development in building the potential for religious awareness that has not been fulfilled.Keywords: film, web series, animation, cinematography, Islamic education, children education medium